Comparison of Intraoperative Three-Dimensional Doppler Color Flow Mapping to Assess Mitral Regurgitation - Hien, Maximilian; Weymann, Alexander; Rauch, Helmut; Großgasteiger, Manuel; Motsch, Johann; Rosendal, Christian (Echocardiography, 2012)
Background: Three-dimensional (3D) transesophageal echocardiography (TEE) enables the determination of the vena contracta area (VCA), which is an approved parameter to quantify mitral regurgitation (MR). The aim of this study was to determine the VCA in the operative setting and to compare it to alternative 3D and standard 2D methods, with respect to different etiologies of MR. Methods: MR in 56 consecutive patients undergoing cardiac surgery was evaluated using 2D and 3D TEE. VCA, vena contracta (VC), and effective regurgitation orifice area (EROA) by 3D and 2D flow convergence methods were determined. The correlations among the methods and the determined areas were evaluated. Results: EROA determination using 3D flow convergence areas correlated strongly with VCA (r = 0.653), however the resulting areas were considerably smaller. VC measurements in the 3D data set correlated slightly less (r = 0.629). EROA, which was determined using 2D flow convergence areas, showed the strongest correlation among the 2D methods (r = 0.406). 2D VC measurements showed weak to no correlation with VCA. Although a correlation was detected when using the biplane method or the midesophageal long-axis view to measure VC, statistical significance was only reached in functional MR and MR due to simple prolapse. Conclusions: Intraoperative 3D methods to determine MR were feasible and showed improved correlation with VCA compared to 2D measurements. The agreement of 2D methods with VCA declined from functional MR to MR due to prolapse. We recommend the utilization of 3D color Doppler for intraoperative evaluation of MR, especially in patients with complex mitral valve prolapses.
First published: 08 May 2012
Gesehen am 19.06.2018